Detection of 2, 4-D in groundwater in northeast of the Yucatan Peninsula - Cejudo, Eduardo; Leal-Bautista, Rosa María; Smith, Daniel N. I.; Grimaldo-Hernández, Cinthya D. (Ecosistemas y Recursos Agropecuarios, 2021)
Herbicides are used to increase the yield of crops and pastures. The herbicide 2, 4-D has high leaching potential in karstic environments because it is water soluble, which causes that the herbicide has been found in groundwater and submerged caves in the Yucatan Peninsula. We detected the presence of the herbicide in groundwater in agricultural non-agricultural zones in the northeaster of the Yucatán Peninsula by using the UV spectrum obtained from HPLC-DAD as qualitative indicator. This finding supports the notion that application of 2, 4-D before and during the wet season promotes the presence of the herbicide in groundwater.